The Quiet Global Revolution of Elite Private Higher Education - Altbach, Philip (International Higher Education, 2023)
In the past half-century and especially since the new millennium, there has been a small but remarkable development of high quality nonprofit private universities, especially in the Global South. These new “elite” universities in countries like Brazil, India, and some others provide new ideas about higher education. Many are funded by philanthropy and are a new area of private higher education.